HISTOPATHOLOGICAL PICTURE OF WHITE RATS LIVER DUE TO THE ADMINISTRATION OF MIMOSIN FROM SIMPLISIA LEUCAENA LEAF - Anjani, Fauzia Hadista; I Ketut Berata,; Siswanto,; Luh Made Sudimartini,; Ni Luh Eka Setiasih,; I Nyoman Sulabda, (Buletin Veteriner Udayana, 2024)
Leucaena leaves (Leucaena leucocephala) are widely used as cattle feed because they contain high protein, flavonoids, tannins and other beneficial substances. In addition to containing good animal feed ingredients, it turns out that leucaena leaves contain toxic ingredients called mimosin. This study aims to study the impact of mimosin on the liver of experimental animals. The study used white rats (Rattus norvegicus) male wistar, aged 2 months with a body weight of 300-350 g, as many as 20 heads divided into 4 treatment groups. The 4 treatment groups were negative control (P0), positive control was given pure mimosin 5 mg/head/day (P1), group was given mimosin from leucaena leaf simplisia 50 mg/head/day (P2), group was given mimosin from leucaena leaf simplisia 150 mg/head/day (P3). Each treatment was given orally for 14 days. On day 15, a necropsy was performed and then the liver was taken and then put into neutral 10% formalin buffer (NBF) for further histopathology using Hematoxylin and Eosin (HE) staining. Histopathological examination is carried out covering five lesion variables, namely fatty degeneration, congestion, bleeding, inflammation, and necrosis. The severity of the lesion was scored, namely score 0 (normal), score 1 (mild), score 2 (medium) and score 3 (severe). The histopathological examination data were then analyzed using the Kruskal-Wallis non-parametic test and the Mann-Withney follow-up test. Based on the results of the study, administration of pure mimosin 5 mg and simplisia of leucaena leaves 50 mg and 150 mg caused histopathological lesions of rat liver (Rattus norvegicus) in the form of fatty degeneration, congestion, bleeding and inflammation that were significant compared to controls, except necrosis lesions. There was no significant lesion difference between mimosin from leucaena leaf simplisia between doses of 50 mg/head/day and 150 mg/head/day. It is necessary to carry out further research on the administration of mimosine in leucaena leaf simplicia at higher doses and given over a longer period, so that the factors of acute and chronic toxicity due to mimosine from leucaena leaves are known.